Inverse structure for active noise control and combined active noise control - Bouchard, M.
In this paper, a simple inverse structure for multichannel active noise control (ANC) is introduced, based on the use of noncausal models of the (pseudo-)inverse plant between the error sensors (typically microphones in ANC systems) and the actuators (typically loudspeakers). This structure, combined with adaptive FIR filters and filtered-x LMS-based algorithms, can produce both a reduction of the computational load and an increase of the convergence speed, compared to the multichannel filtered-x LMS algorithm or its fast exact realizations. Also, for systems combining active sound cancellation and exact sound reproduction (such as headphones combining both ANC and binaural audio with equalization), the proposed inverse structure can further reduce the computational load compared to common approaches. Simulations using exact and noisy models of a realistic acoustic plant and an inverse plant were performed to verify the performance of the proposed structure
Keywords: Acoustic plant; Active sound cancellation; Actuators; Adaptive FIR filters; Binaural audio; Combined active noise control/sound reproduction systems; Computational load; Convergence speed; Equalization; Error sensors; Exact sound reproduction; Filtered-x LMS-based algorithms; Inverse modeling; Inverse plant; Inverse structure; Loudspeakers; Microphones; Multichannel active noise control; Noncausal models; Performance; Simulations